The Impact of Animation Video Media on the Ability to Write Explanatory Texts of Class VIII MTs Rahmat Sa'id Bongkot Students - Ayyu Subhi Farahiba; Umi Fadhilah (Universitas Muhammadiyah Enrekang, 2024)
This research is motivated by the lack of students' ability to write explanatory texts. Application of YouTube animated video learning media to reduce students' weak writing abilities. The purpose of this study was to determine the effect of YouTube animated video media on the skills of writing explanatory texts for class VIII MTs Rahmat Sa'id Bongkot in terms of structure and linguistic rules. This study used a Quasi-Experimental Design quantitative research method with a Nonequivalent Control Group design. This study used a sample of class VIII A as the control class and VIII B as the experimental class. Data collection techniques used are tests, questionnaires, and observation sheets. Prerequisite tests in this study used the normality test, homogeneity test, and T test. In calculating the normality test data, the experimental class pretest 0.12 < 0.294 and the experimental class posttest 0.138 < 0.294 were categorized as normally distributed. The results of the data calculation pretest control class 0.19 <0.287 and posttest control class 0.115 <0.294 are categorized as normally distributed. Homogeneity test pretest 1.466 <2.137 and posttest 1.565 <2.137 categorized as homogeneous. T test 2.512 > 2.093 then Ho is rejected and Ha is accepted. Based on the results of the prerequisite test calculations, there is an influence of YouTube animated video media on the ability to write explanatory text.